Characterization of microplastics in human follicular fluid and assessment of their potential impact on mouse oocyte maturation in vitro - Danyu Ni; Kaidi Yu; Nan Yan; Xiaojiao Chen; Qijun Xie; Yuqin Yang; Wei Jiang; Ye Yang; Junqiang Zhang; Xiufeng Ling (Ecotoxicology and Environmental Safety)
Microplastics (MPs) have been identified in various human tissues and organs. This study aims to evaluate the presence of MPs in human follicular fluid (hFF) and their potential impact on oocyte maturation. Laser direct infrared spectroscopy of 19 hFF samples identified 7956 particles, including 1739 microplastics (21.9 %) from 30 types. Of these, 923 particles had matching degrees > 0.8, and 7033 had matching degrees between 0.65 and 0.8. The most abundant MPs were Chlorinated Polyethylene (CPE), Fluorosilicone rubber, Polyvinyl chloride (PVC), Butadiene rubber (BR), and Styrene-butadiene-styrene (SBS), with diameters ranging from 20 to 100 μm. Five random samples were analyzed by pyrolysis-gas chromatography-mass spectrometry, which detected four types of microplastics—Polyethylene (PE), Polypropylene (PP), Polystyrene (PS), and PVC—at varying concentrations. PE was the most abundant (22.284 mg/kg), followed by PVC (1.061 mg/kg), PP (0.837 mg/kg), and PS (0.600 mg/kg). Based on the diameter and concentration ranges of MPs in hFF, we used seven types of fluorescence-labeled MP beads—PE, PVC, PP, PS, CPE, Polymethylmethacrylate (PMMA), and Polytetrafluoroethylene (PTFE)—to assess their impact on mouse oocyte in vitro maturation. The results showed that smaller MP beads (e.g., 50 μm PE) were more likely to penetrate the zona pellucida and enter the oocyte, while larger beads (e.g., 500 nm PMMA) tended to adhere to the zona and remain outside the oocyte. All seven types of MP beads hindered oocyte maturation, resulting in varying reductions in maturation rates compared to the control group. Our findings suggest that MPs contaminate hFF and may impair oocyte maturation.